Upaya Peningkatan Kesadaran dan Aksi Nyata Dalam Pengelolaan Lingkungan Desa Sidomulyo Barat Kelurahan Sidomulyo Barat - Murialti, Neng; Ramadhan, Sutan Rizky; Daratullaila, Intan; Sihombing, Nuraini; Purba, Julia Noranda; Wiratama, Budi; Bastiansyah, Bastiansyah; Adinda, Trina; Gaol, Ivana Lumban; Maulaya, Raihan Akbar; Sahana, Ruth; Hatauruk, Cathrine Angelia; Marito Siregar, Jojor Lima; Amwat, Muhammad; Asparenza, Wina; Putra, Ferdi Hadi; Diningsih, Tefra; Dzaky H, M. Habib; Prayogo, Alvin; Fitriani, Yuli; Indriyani, R. Retno; Baghtiar, Tian (Jurnal Ilmiah Wahana Pendidikan, 2024)
KKN is a real action from students as a form of community service. The purpose of this activity is how students can help solve phenomena that exist in society, especially those related to the environment where they live, especially related to inorganic waste management. As is well known, an organic waste if not managed properly can damage the environment on the one hand, but on the other hand it can be used for environmental sustainability and beauty and can even be used as a source of additional income for households through creative management properly and correctly. Implementation of KKN group 15 which was carried out in West Sidomulyo Sub-District in RW 26 at RT I, II and III with "awareness raising efforts and real action in environmental management" in the form of an organic waste management to become "Paving Block". This activity can reduce the negative impact of inorganic waste scattered around people's homes. So as to create a clean and comfortable environment that will have an impact on improving the quality of life of the community both in terms of health and the economy.